Bhagottar Gutika (Herbo-Mineral Formulation): An Overview - Mishra, Meenu (International Research Journal of Ayurveda & Yoga, 2022)
Respiratory diseases are become a universal concern due to its chronic nature and unwanted modern remedy which causes dose dependency and long term side effects. In Ayurveda Rasaushadhi, which translates into herbo-mineral formulation is the most important medication by its quick action in low doses with easier palatability. Bhagottar Gutika is one of them which contains Purified Mercury, Purified Sulphur, Piper longum, Terminalia Chebula, Terminalia Bellirica, Adhatoda Vasica, Clerodendrum serratum, Acacia Arabica in increasing quantity. This review article documents the indications, method of preparation, probable mode of action and properties of Bhagottar Gutika. This study concluded the antibacterial, anti-inflammatory, bronchodilator and immune-enhancer effects of Bhagottar Gutika. So, it can be used as an effective medicine for bronchitis and bronchial asthma.